2002
DOI: 10.1007/s00424-002-0884-z
|View full text |Cite
|
Sign up to set email alerts
|

Components of pacemaker potentials recorded from the guinea pig stomach antrum

Abstract: Pacemaker potentials recorded intracellularly from the guinea pig stomach consisted of initial primary and following plateau components. Inhibition of the internal Ca2+ store pump with cyclopiazonic acid depolarized the membrane and inhibited the plateau component of pacemaker potentials. 2-aminoethoxydiphenyl borate (an inhibitor of IP3-induced Ca2+ release) and carbonyl cyanide m-chlorophenyl-hydrazone (a mitochondrial protonophore) depolarized the membrane and abolished pacemaker potentials. Low [Ca2+]o sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
163
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(183 citation statements)
references
References 52 publications
20
163
0
Order By: Relevance
“…Amongst the latter parameters, the Q10 values for the duration ranged between 1.6 and 2, while those for the dV/dt and latency were over 2. The rising phase of pacemaker potentials may depend upon the activation of Ca 2+ -permeable channels which are not sensitive to nifedipine but are sensitive to Ni 2+ or to voltage change Hirst et al, 2002b;Kito et al, 2002a;Kito and Suzuki, 2003a). If the Ca 2+ -permeable channel has a Q10 value similar to that for other ion channels, then the high Q10 value for dV/dt suggests the contribution of unidentified additional temperature-dependent factors in determining the speed of the upstroke phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst the latter parameters, the Q10 values for the duration ranged between 1.6 and 2, while those for the dV/dt and latency were over 2. The rising phase of pacemaker potentials may depend upon the activation of Ca 2+ -permeable channels which are not sensitive to nifedipine but are sensitive to Ni 2+ or to voltage change Hirst et al, 2002b;Kito et al, 2002a;Kito and Suzuki, 2003a). If the Ca 2+ -permeable channel has a Q10 value similar to that for other ion channels, then the high Q10 value for dV/dt suggests the contribution of unidentified additional temperature-dependent factors in determining the speed of the upstroke phase.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the Q10 value for duration was comparable to those for ion channels. The plateau component (Kito et al, 2002a) and slow potentials (Hirst et al, 2002a) (Hashitani and Brading, 2003). Thus, it is possible that the factors responsible for the temperature-dependent change in the duration of slow waves are the properties of ion channels and intracellular [Ca 2+ ]i.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion was based on pharmacological tests using a Cl -channel-blocking drug (4-acetoamido-4-isothiocyanat-ostilbene-2,2-disulphonic acid; SITS). From studies of intact muscle preparations, other investigators have suggested that Ca 2+ -activated Cl -conductance is responsible for the pacemaker currents in ICCs (Hirst et al, 2002;Kito et al, 2002). These investigators have suggested that Ca 2+ released from IP3…”
Section: Possible Mechanisms For the Pacemaker Activity In Interstitimentioning
confidence: 99%
“…In the gastric wall of laboratory animals such as the guinea-pig and mouse, many types of ICC are identified, such as those distributed within the myenteric plexus (ICC-MY), within the circular smooth muscle layers (ICC-IM) and within the submucosal plexus (ICC-SM) (Komuro et al, 1996;Burns et al, 1997). In the guinea-pig, ICC-MY generate driving potentials with initial fast transient (duration, 1-2 s) and subsequent plateau components (duration, 10-15 s), and the potentials are propagated to circular and longitudinal smooth muscle layers in an electrotonic manner through gap junctions (Dickens et al, 1999;Kito et al, 2002b). These slow waves consist of both voltage-sensitive and voltage-insensitive components (Ohba et al, 1975;Tomita, 1981), with only the former easily inhibited by caffeine (Dickens et al, 1999;Suzuki and Hirst, 1999).…”
Section: Introductionmentioning
confidence: 99%